Representações sociais de um grupo de professores sobre a educação inclusiva - Lima, Renata Cristina Domingos de Souza (2011)
Inclusive education appears in the exponent of education as a way of guaranteeing the right of access to education for all citizens. However, after about seventeen years of discussions about school inclusion, this process has failed to materialize, so that many children are still out of school and others, although they are attending school spaces, not show satisfactory educational development. Given this scenario and the need to better understand the meanings of teachers on inclusive education, this research aimed to understand the social representations of a group of teachers on inclusive education. The study was conducted with ninety elementary school teachers in the public system of a city in the countryside of São Paulo. Technique was used in free association from the terms of special education, special educational needs and inclusive education, and data were analyzed using the EVOC software and a questionnaire incomplete sentences, and data were processed using the technique of content analysis. The theoretical basis for understanding the data was the Theory of Social Representations. The analysis points to a consistency and homogeneity of the group discussion of teachers, suggesting that the representation of inclusive education as a core organizer has the concept of equality and uniformity. The concept of inclusive education seems to be associated with the disabled student, who flees to standards devised by the group. This, in turn, seems to perceive the teacher as unprepared to deal with inclusion and coated with feelings of fear and insecurity. The strategies that seem to be available by the group are dealing with the inclusion of attitudinal and affective order, revealing passivity and offset each other of responsibility for inclusive actions